Features of rational and modern interpretation in the interpretation of Sheikh Muhammad al-Khal - Rasoulnejad, Dr. Abdullah (Sulaimani Journal for Humanities, 2023)
The Qur’an, by calling for reflection on the signs in the horizons and within ourselves, has instilled in the souls of Muslims a love of science and knowledge. They have begun to derive from it directly many sciences, such as the science of interpretation, which is considered one of the noblest sciences, and thousands of interpretations have been written in various styles and in different languages. Because the Muslim peoples who embraced Islam and entered it willingly were influenced by Islam and its lofty concepts, the comprehensiveness and humanity of that culture provided an opportunity for the Muslim peoples to interact and respond to it, so they participated in enriching it with committed intellectual and emotional products that expressed the conscience of Islam, and resulted from a sincere human experience that went beyond the scope of imitation to contribute to the extent of creativity, creation and innovation, and scholars appeared among the Muslim peoples in all fields of Islamic sciences, so that Ibn Khaldun says: It is strange that the bearers of knowledge in the Islamic nation are mostly non-Arabs, and among those peoples, as Sheikh Al-Khal says: the noble Kurdish people who embraced Islam from the depths of their hearts and the core of their souls, and from among their sons emerged scholars and writers who exceed the limit and counting; They had a clear and invaluable role in spreading the Islamic religion, supporting Arabic culture, documenting its sciences and literature, standardizing its linguistic rules, and unveiling its secrets. Until recently, Kurdish scholars were a cornerstone in the building of Islamic civilization. Among these scholars was Sheikh Muhammad al-Khal, a multifaceted scholar and writer with numerous scientific and literary works, including his valuable commentary in Kurdish. This commentary is no less valuable than the well-known modern commentaries in the Islamic world, and it is characterized by its rational, modern, and innovative approach. It addresses contemporary issues such as combating ignorance and backwardness, defending women's rights, and motivating the people to achieve progress in accordance with the demands of the age. It also discusses new scientific topics and modern terminology such as democracy, socialism, and the like. This brief research, using a descriptive and analytical method, aims to highlight the most important rational and modern features of this valuable commentary. And a statement of the most important similarities between Al-Khal’s views in his interpretation and the interpretive views of the modern interpretive school, such as Sheikh Muhammad Abduh, Sheikh Muhammad Rashid Rida, and Sheikh Mustafa Al-Maraghi.
Keywords: Interpretation and its types; AlKhals interpretation; his interpretive views; modern features; the modern school of interpretation